2014
DOI: 10.1371/journal.pone.0098991
|View full text |Cite
|
Sign up to set email alerts
|

Venom Variation during Prey Capture by the Cone Snail, Conus textile

Abstract: Observations of the mollusc-hunting cone snail Conus textile during feeding reveal that prey are often stung multiple times in succession. While studies on the venom peptides injected by fish-hunting cone snails have become common, these approaches have not been widely applied to the analysis of the injected venoms from mollusc-hunters. We have successfully obtained multiple injected venom samples from C. textile individuals, allowing us to investigate venom compositional variation during prey capture. Our stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Variations in the more biologically relevant injected venom of the fishhunting species C. striatus, C. catus [16], Conus consors [19], Conus ermineus [20], and Conus purpurascens [21] have been reported. Variations within an individual specimen's injected venom over time (C. consors [19], C. textile [22], C. purpurascens [21]) have also been observed. All these studies use conventional bioanalytical approaches that lead to the characterization of the major components of the venom.…”
Section: Introductionmentioning
confidence: 92%
“…Variations in the more biologically relevant injected venom of the fishhunting species C. striatus, C. catus [16], Conus consors [19], Conus ermineus [20], and Conus purpurascens [21] have been reported. Variations within an individual specimen's injected venom over time (C. consors [19], C. textile [22], C. purpurascens [21]) have also been observed. All these studies use conventional bioanalytical approaches that lead to the characterization of the major components of the venom.…”
Section: Introductionmentioning
confidence: 92%
“…This has been previously observed with other ant species such as Odontomachus haematodus 80 , Dinoponera quadriceps 53 and other venomous organisms including marine cone snails 11 and wasps 64 . The reason for these marked differences has been attributed to different factors such as age, size, differential gene expression, altered post-translational modifications and, in the case of ants, genetic polymorphisms that result from the queens mating with different males during their lifetime 64,81 . It has also been previously shown that although the organisms are from the same region, as was the case with these colonies, slight environmental differences between the two colonies may explain the differences seen 53,64 .…”
Section: Inter-colony Variationsmentioning
confidence: 99%
“…The shape and number of barbs of the hollow radular tooth as well as the feeding behavior of cone snails appear to be, at least in some cases, adapted to capturing most efficiently the different types of prey. For instance, some molluscivorous cones make successive injections of radular teeth into the prey ( Prator et al. 2014 ) whereas piscivorous cones show up to three different hunting modes including electrical stunning and tethering of single preys using the proboscis, engulfing of several prey fish at once by the rostrum, and flailing the proboscis around the fish without tethering ( Olivera et al.…”
Section: Introductionmentioning
confidence: 99%